(untitled) (Journal of the College of Basic Education, 2026)
This study aims to examine the effect of text-linguistics-based instruction on EFL undergraduate students’ use of cohesion devices and their ability to construct coherent academic texts. The study was conducted with 120 second-year students at the University of Baghdad employing a single-group pretest–post-test experimental design. Students completed free writing tasks before and after a six-week intervention grounded in Cohesion in English. Data were analysed using dependent t-tests in SPSS 15.0. Results revealed a significant increase in total cohesion device usage from M=81.96 (SD=19.52) to M=91.48 (SD=21.56), t=3.260, p=.001, with a moderate effect size (d=0.46). Significant improvements were found in ellipsis (p=.002) and substitution (p=.031), while changes in lexical cohesion and reference were not statistically significant (p>.05). Coherence scores increased slightly from M=2.78 to M=2.83; however, this difference was not significant (p=.265). The findings indicate that text-linguistic intervention effectively enhances cohesion use but has limited impact on overall coherence development.